Clinical Symptoms, Endoscopic and Stroboscopic Imaging in Patients with Laryngeal Fungal Infection in Relation to Fungal Identification Result - Thi Linh Trang, Ngo; Dinh Thi, Dao; Tuan Son, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
This paper aims to describe the similarities and differences in fungal laryngitis’ clinical characteristics, endoscopic, and stroboscopic imaging between patients with positive and non-positive fungal identification results. The study enrolled 48 patients diagnosed with fungal laryngitis by the Endoscopy Department in the National ENT Hospital of Vietnam from August 2019 to March 2020. The study results show that the patients in both groups had dysphonia (100%), with insignificant difference in the severity. However, the patients in the Positive group were more likely to go to hospital right in the first month of the symptom (55%), whereas the patients in the Non-positive group usually waited for more than 3 months (57.1%), (p<0.05). In endoscopic imaging, fungal pseudomembrane could be found mainly on the vocal cords in both groups, with instances spreading to the subglottis (15%) and trachea (5%) in the Positive group (p<0.05). The tissue layer of the patients in the Positive group was mostly inflamed, meanwhile the patients in the Non-positive group were more prone to swelling tissue (67.9%), (p<0.05). In stroboscopic imaging, the difference was minimal. The patients in the Positive group were more likely to lose the mucosal wave formation (60%) than in the Non-positive group (46.4%). There were also insignificant differences in the mucosal wave’s characteristics: asymmetry (50% in the Positive group; 66.7% in Non-positive group), diverse periodicity (50% in the Positive group; 33.3% in the Non-positive group). The paper concludes that there were differences between the two groups of patients and the clinical, endoscopic and stroboscopic findings, fungal identification should be further implemented for definitive diagnosis in patients with fungal laryngitis.   Keywords Fungal laryngitis, dysphonia, endoscopic imaging, stroboscopic imaging, fungal identification. References [1] G.D. Brown, D.W. Denning, N.A.R. Gow, and S.M. Levitz, Hidden killers: Human fungal infections. SciTransl Med (4) (2012) 1-6. https://doi.org/10.1126/scitranslmed.3004404 [2] M. Pal, Veterinary and medical mycology. 1st ed. New Delhi: Indian Council of Agricultural Research, 2007. [3] H. Luong, Diagnosis and treatment in patients with fungal laryngitis, Doctoral thesis, Hanoi Medical University, 2004. [4] D. Thai, D. Nguyen, Diagnosis and treatment in fungal laryngitis, Ho Chi Minh Med 15(1) (2011) 222-227. [5] J. Guinea, and M. Torres - Narbona, Pulmonary aspergillosis in patients with chronic obstructive pulmonary disease: incidence, risk factors, and outcome. Clin Microbiol Infect. 16 (7) (2010) 870-877. https://doi.org/10.1111/j.1469-0691.2009.03015.x [6] J.M. Wood, Theodore Anthanasiadis, and Jacqui Allen. 2009. Laryngitis. BMJ (349) (2009) 5827. https://doi.org/10.1136/bmj.g5827. [7] A. Chindamporn, A. Chakrabarti, and R. Li, Survey of laboratory practices for diagnosis of fungal infection in seven Asian countries: An Asia Fungal Working Group (AFWG) initiative, Med Mycol 56 (2018) 416 - 425. https://doi.org/ 10.1093/mmy/myx066 [8] R. Pribuisiene, V. Uloza, and P Kupcinskas, Perceptual and acoustic characteristics of voice changes in reflux laryngitis patients. J Voice 20 (1) (2006) 128 - 136. https://doi.org/10.1016/j.jvoice.2004.12.001.